Predicting The Risk of Cardiovascular Complications of Cardiovascular Pathology in Patients with Psoriatic Arthritis - Abdullaev Ulugbek Sayfullaevich (Genius Publishing Group, 2023)
According to current researchers, one of the most common comorbid diseases in patients with psoriatic arthritis (PsA) is cardiovascular pathology (CVP). The trend frequency of cardiovascular pathology (CVP) has a high probability of developing cardiovascular complications (CVC), which leads to early disability in PsA patients. This is the reason for in-depth analysis of risk factors and predicting the risk of cardiovascular complications (CVC) in PsA patients.
Keywords: Psoriatic arthritis; cardiovascular complications; cardiovascular pathology